2022
DOI: 10.3389/fonc.2022.903157
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Ketone Replacement Does Not Improve Survival or Cancer Cachexia in Mice With Lung Cancer

Abstract: Cachexia is a debilitating comorbidity affecting many lung cancer patients. We have previously found that cachectic mice with lung cancer have reduced serum ketone body levels due to low PPARα activity in the liver. Restoring hepatic PPARα activity with fenofibrate increased circulating ketones and delayed muscle and white adipose tissue wasting. We hypothesized that the loss of circulating ketones plays a pathophysiologic role in cachexia and performed two dietary intervention studies to test this hypothesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 48 publications
0
11
1
Order By: Relevance
“… 33 Our results contradict recent reports showing that KD did not prevent cachexia in a KRAS‐driven murine lung cancer model, a heterotopic C26 colon cancer model or the autochthonous genetically engineered KPC PDAC model. 16 , 34 , 35 Furthermore, KD delayed tumour growth in the latter two models, yet we observed no effect of KD on tumour size. These discrepant results could be explained by differences in the KD interventions or duration of KD feeding.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“… 33 Our results contradict recent reports showing that KD did not prevent cachexia in a KRAS‐driven murine lung cancer model, a heterotopic C26 colon cancer model or the autochthonous genetically engineered KPC PDAC model. 16 , 34 , 35 Furthermore, KD delayed tumour growth in the latter two models, yet we observed no effect of KD on tumour size. These discrepant results could be explained by differences in the KD interventions or duration of KD feeding.…”
Section: Discussionmentioning
confidence: 43%
“… 12 , S2 , S3 This is potentially because most studies evaluating cancer cachexia compare patients or mice with fully developed cachexia against healthy control populations. 13 , 14 , 15 , 16 , 17 , 18 Thus, the early biology driving initial wasting, which may differ from the inflammation‐driven biology defined in more advanced cachexia, is not well characterized. 6 Indeed, a recent study of early murine PDAC cachexia, using the autochthonous KPC model, showed no elevations in cachexia‐associated cytokines and was unable to discriminate cachexia from pure undernutrition.…”
Section: Introductionmentioning
confidence: 99%
“…The primary PubMed search resulted in 184 hits of which 156 were discarded after title, abstract, or full-text screening, resulting in 28 articles for inclusion [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] . An additional 15 articles were retrieved from my personal library [20] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Thomsen et al present human data showing that infusion with BHB reduces muscle protein catabolism, which supports our in vitro observations (Thomsen et al, 2018). However, a separate, recent study in NSCLC showed that ketogenic diet was not sufficient to prevent tumor progression and cachexia development (Langer et al ., 2022). These apparently contradictory responses to ketogenic diet highlight the likelihood that cachexia can result from different underlying mechanisms, which may be susceptible to unique therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Cachexia is clinically defined by certain thresholds of weight and muscle loss (Fearon et al ., 2011), and most studies evaluating cancer cachexia compare mice with fully developed cachexia against healthy control populations (Arneson-Wissink et al, 2020; Langer et al, 2022; Michaelis et al, 2017; Talbert et al, 2019). Because of the focus on advanced disease, the pre-cachectic state remains poorly defined.…”
Section: Introductionmentioning
confidence: 99%